2009
DOI: 10.1002/pro.149
|View full text |Cite
|
Sign up to set email alerts
|

Charge neutralization and collapse of the C‐terminal tail of alpha‐synuclein at low pH

Abstract: Alpha-synuclein (aS) is the primary component of Lewy bodies, the pathological hallmark of Parkinson's Disease. Aggregation of aS is thought to proceed from a primarily disordered state with nascent secondary structure through intermediate conformations to oligomeric forms and finally to mature amyloid fibrils. Low pH conditions lead to conformational changes associated with increased aS fibril formation. Here we characterize these structural and dynamic changes using solution state NMR measurements of seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 56 publications
12
98
0
Order By: Relevance
“…Instead, intermolecular electrostatic repulsion of the negatively charged C-terminus, hydrophobicity, and overall structural compactness may play a more prominent role in oligomerization [54][55][56][57]. For example, using single-molecule (sm) fluorescence resonance energy transfer (FRET), it was demonstrated that at low pH, charge neutralization at the C-terminus increases intramolecular contacts and allows inclusion into a hydrophobic cluster that is more aggregation prone [56].…”
Section: Intramolecular Interactions As Determinants Of Aggregationmentioning
confidence: 99%
“…Instead, intermolecular electrostatic repulsion of the negatively charged C-terminus, hydrophobicity, and overall structural compactness may play a more prominent role in oligomerization [54][55][56][57]. For example, using single-molecule (sm) fluorescence resonance energy transfer (FRET), it was demonstrated that at low pH, charge neutralization at the C-terminus increases intramolecular contacts and allows inclusion into a hydrophobic cluster that is more aggregation prone [56].…”
Section: Intramolecular Interactions As Determinants Of Aggregationmentioning
confidence: 99%
“…However, subsequent studies indicated that the E46K mutation increases such contacts, and that they are unaffected by the A30P and A53T mutations. Other conditions that increase the compactness of regions of the protein also lead to enhanced aggregation (34) whereas variants or conditions that reduce long-range interactions are associated with reduced aggregation (35, 36), Thus, it seems that long-range contacts may not be protective against aS aggregation and might even facilitate the process (37). …”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the aggregation propensity of α-synuclein is very sensitive to solution conditions such as temperature, pH, salt concentration, and solution cofactors. There has been significant work to discover the structures that form in association with lipids, structures of final aggregates, and structures that may be the aggregation precursor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the underlying reason for why monomeric α-synuclein is so prone to aggregation is still unknown.…”
mentioning
confidence: 99%